Penerapan Pola Pemberdayaan Berpikir Melalui Pertanyaan dalam Model Pembelajaran Two Stay Two Stray untuk Meningkatkan Aktivitas dan Hasil Belajar pada Mata Kuliah Mikrobiologi Terapan - Murti, Warda; Anas, Muh (Biology Teaching and Learning, 2019)
Abstract. This study aims to determine the application of Thinking Empowerment Patterns Through Questions (PBMP) in the Two Stay Two Stray learning model (TSTS) to improve activities and learning outcomes in applied microbiology courses in Biology Education Study Program Faculty of Teacher Training and Education UMMA. This type of research is a class action research (Class Room Action Research) which involves repetitive or cyclic reflection. The subjects of this study were students of biology education study programs who were taking courses in Applied Microbiology in the even semester of the 2018/2019 academic year. Data collection techniques in this study were carried out by observation and test techniques. The learning outcomes test was carried out at the end of each cycle to determine the extent of student understanding of the material provided. The collected data is then analyzed using percentage techniques, descriptive statistics, and qualitative analysis. The results of this study are patterns of empowerment of thinking through questions in the two stay two stray learning model can improve student learning activities and outcomes. Keywords: PBMP, TSTS model, learning activities, learning outcomes